COLLABORATIVE BUSINESS MODEL FROM THE PERSPECTIVE OF VALUE NETWORK - Mochamad Sandy Triady, Dina Dellyana , Ami Fitri Utami (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Indonesia has an abundant asset of cultural and craft products as the country comprises of profoundly diverse ethnic groups and tribes. However, numerous cultural and art products are hardly persevering to exist. In this study, we examined an approach to answer the problem, where different shareholders have worked together to incorporate and develop a collaborative business model, expectedly may optimize the potential of the local creative economy. This research was conducted under a qualitative study wherein the author observed the actual condition and phenomenon on site. It was revealed that collaboration might increase the value added for each party; furthermore, make the business more sustainable. The state leads to economic growth since the production process is conducted ethically fair.